The Role Of Financial Managers And Sharia Actualization - CheffyNofiana Meuraxa; Maylia Santika; Della Annisa (Proceeding International Seminar of Islamic Studies, 2019)
This article discusses the role of financial managers and the actualization of Sharia. Financial managers play an important role in financial management decision making. Sharia financial managers are directed to optimize the value of the company in accordance with syara '. A financial manager is someone in charge of planning, budgeting, checking, managing, and storing funds owned by a company. Financial decisions are also the responsibility of the financial manager. The purpose of financial managers is to be able to generate corporate profits, be able to improve welfare, be able to increase company value, and be able to improve the company's image. The financial manager is also responsible for obtaining a smooth flow of cash into the company to finance investment and company operations depends on the extent to which the financial manager's ability to carry out the funding function.